Exchange rate misalignments: A comparison of China today against recent historical experiences of Japan, Germany, Singapore and Taiwan - Xinhua He; Duo Qin; Yimeng Liu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
The familiar claim of Chinese currency manipulation is generally asserted without reference to empirical evidence. To investigate the legitimacy of the claim, we ask if the undervalued misalignment found in the real effective exchange rate (REER) of the Chinese renminbi (RMB) over the past decade has any recent historical precedents. Four cases are examined: the Japanese yen, the Deutsche mark, the Singapore dollar and the Taiwan dollar. Panel-based misalignment estimates of the REER of the four currencies are obtained using quarterly data from the late 1970s to the early 2000s. Our estimates suggest that there are precedents to the recent misalignment of the RMB in terms of magnitude, duration or breadth of currency coverage, and that a net build-up in foreign asset does not necessarily result in currency misalignment. In addition to finding little empirical justification for the claim of Chinese currency manipulation, we note that REER misalignment runs a risk of propagating inflation in the home economy.
URN:NBN:fi:bof-201408072032
Keywords: 330